Low-creep high-alumina brick based on electric melting a-beta corundum brick waste and preparation method of low-creep high-alumina brick

By using the combination of electromelted a-β corundum brick waste and other mineral powders, high-performance low-creep high-alumina bricks are prepared, which solves the problems of reducing raw material resources and high costs in the existing technology, and achieves significant improvement in product performance and effective utilization of resources.

CN119661240AActive Publication Date: 2025-03-21CHINA FIRST METALLURGICAL GROUP +2
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411837875.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-03-21
Estimated Expiration
2044-12-13

AI Technical Summary

Technical Problem

The raw materials of existing low-creep high-alumina bricks mainly rely on bauxite, resulting in reduced resources, high costs and unstable quality, making it difficult to produce high-performance low-creep high-alumina bricks.

Method used

Electromethy a-β corundum brick waste is used as the main raw material, combined with 85 bauxite particles, rosy fine powder, silica stone fine powder, electromethy corundum fine powder and Guangxi white mud powder, low-creep high-alumina brick is prepared through specific mixing and sintering processes.

Benefits of technology

The obtained low-creep high-alumina brick has good microstructure, stable product quality, high compressive strength, good thermal shock performance, low creep rate, far better than traditional high-alumina bricks, and has achieved resource utilization of waste and reduced production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005187206980000061
    Figure BDA0005187206980000061
Patent Text Reader

Abstract

The invention discloses a low-creep high-alumina brick based on electric melting a-beta corundum brick waste and a preparation method thereof, and belongs to the technical field of high-alumina bricks. The low-creep high-alumina brick comprises the following raw material components in percentage by mass: 20-30% of electric melting a-beta corundum brick waste with the particle size of 0-3.5 mm; 20 to 30 percent of 85 bauxite particles; 10-20% of fine andalusite powder; 10%-20% of sillimanite fine powder; 0-15% of fused corundum fine powder; 0-15% of Guangxi white mud powder; and 2-5% of an additive which is externally doped. The obtained low-creep high-alumina brick is good in microstructure, stable in product quality, high in compression strength, good in thermal shock performance and low in creep rate and is far superior to similar high-alumina bricks, the performance of the low-creep high-alumina brick is greatly improved, and the low-creep high-alumina brick has important application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of high-alumina bricks, and particularly relates to a low-creep high-alumina brick based on fused a-beta corundum brick waste and a preparation method thereof. Background Art

[0002] High alumina brick is a kind of refractory material, its main component is Al2O3, it is mainly formed by combining bauxite clinker, clay fine powder and admixtures, and sintered at high temperature. It has the characteristics of high refractoriness, high strength and certain creep. The main components of low creep high alumina brick are basically the same as those of high alumina brick, but its performance is better than that of high alumina brick, with higher strength, better low creep and better thermal shock resistance. At present, low creep high alumina brick is mainly made of bauxite clinker sintered from ordinary bauxite ore. Bauxite clinker contains corundum phase, mullite phase, glass phase and other impurity phases, with complex composition, which has a complex influence on the various properties of the material, unstable quality, and it is not easy to produce 1400℃ low creep high alumina brick; and the resources of bauxite clinker are decreasing, and the high cost is not conducive to the long-term development of low creep high alumina brick. Summary of the invention

[0003] The purpose of the present invention is to provide a low creep high alumina brick based on fused a-β corundum brick waste and a preparation method thereof. The obtained low creep high alumina brick has good microstructure, stable product quality, high compressive strength, good thermal shock resistance, low creep rate, greatly improving the performance of low creep high alumina brick, and has important application prospects.

[0004] In order to solve the above technical problems, the present invention adopts the following technical solutions:

[0005] Provided is a low creep high alumina brick based on fused a-β corundum brick waste, wherein the raw materials include the following components by mass percentage:

[0006] 20-30% of fused a-β corundum brick waste, with a particle size of 0-3.5mm;

[0007] 85 bauxite particles 20-30%;

[0008] Andalusite fine powder 10-20%;

[0009] Sillimanite fine powder 10-20%;

[0010] Fused corundum fine powder 0-15%;

[0011] Guangxi white mud powder 0~15%;

[0012] Admixture 2-5%, external mixing.

[0013] According to the above scheme, the particle size of the 85 bauxite particles is 0 to 3.5 mm.

[0014] According to the above scheme, the particle size of the andalusite fine powder is ≤0.075mm; the particle size of the sillimanite fine powder is 0-0.2mm; the particle size of the fused corundum fine powder is ≤0.075mm; and the particle size of the Guangxi white mud powder is ≤0.075mm.

[0015] According to the above scheme, the fused a-β corundum brick waste is mainly composed of a-Al2O3 and β-Al2O3 crystal phases. Preferably, a-Al2O3 accounts for 40-50wt% and β-Al2O3 accounts for 45-60wt%.

[0016] According to the above scheme, in the electro-fused a-β corundum brick waste, Al2O3≥93wt%, Na2O+K2O≤1wt%, and Fe2O3≤1wt%.

[0017] According to the above scheme, the fused a-β corundum brick waste is the waste generated by cutting and grinding in the production of fused a-β corundum bricks.

[0018] Fused a-β corundum bricks are high-grade fused refractory materials commonly used in glass kilns for glass in light industry, building materials, electronics and other industries. They are made of high-purity calcined alumina (more than 95%) and a small amount of additives (Na2CO3 and Na2B4O7·10H2O). After mixing, they are put into a three-phase electric arc furnace and cast after high-temperature melting at more than 2300℃. It mainly includes a-Al2O3 and β-Al2O3, of which a-Al2O3 accounts for 40-50% and β-Al2O3 accounts for 45-60%. The crystals of the two are interlaced to form a very dense organizational structure. The interior of the material is >95% corundum phase and glass phase <1%. It has few impurities, high strength, corrosion resistance and good high-temperature performance. At the same time, β-Al2O3 has a loose lattice, forming a void structure on the material, which is more resilient than other Al2O3 phases and can diffuse the energy of the absorbed thermal stress to avoid the energy being unable to be released due to the dense structure, resulting in a sharp increase in the absorbed energy, leading to the breakage of crystal bonds, thereby forming a sharp fracture and peeling of the material, thereby improving the thermal shock performance of the product.

[0019] According to the above scheme, the waste fused a-β corundum bricks are recycled in the following way: the fused a-β corundum bricks discarded during the cutting and grinding process are selected, separated and impurities are removed, then steamed and washed 3-4 times, then blown and dried, and crushed into particles with a particle size of 0-3.5mm, and iron removal is performed during the crushing and pulverization process. Preferably, the Fe2O3 content is controlled within 1%, which can reduce the formation of excessive melt holes on the surface of the product caused by the excessive iron oxide content in the raw material during sintering.

[0020] According to the above scheme, in the 85 bauxite particles, Al2O3≥85wt%, Fe2O3≤1.5wt%, and the refractoriness is ≥1800℃.

[0021] According to the above scheme, 85 bauxite particles are first classified and selected, and then steamed in water for 2 to 3 times, naturally air-dried, and then crushed and ground into powder.

[0022] According to the above scheme, the indicators of the andalusite fine powder are: Al2O3≥55wt%, Fe2O3≤1.5wt%.

[0023] According to the above scheme, the sillimanite fine powder has the following indicators: Al2O3≥56wt%, Fe2O3≤1wt%.

[0024] According to the above scheme, the indicators of the fused corundum fine powder are: Al2O3≥95wt%, Fe2O3≤0.2wt%.

[0025] According to the above scheme, Guangxi white mud powder has Al2O3≥35wt%, Fe2O3≤1.5wt%. Guangxi white mud powder has good plasticity, low impurity content, clear white color and good adhesion.

[0026] According to the above scheme, the additive is dextrin or pulp.

[0027] According to the above scheme, in terms of mass percentage, the low creep high alumina bricks contain 8-15% fused corundum fine powder and 8-15% Guangxi white mud powder.

[0028] A method for preparing the above-mentioned low creep high alumina brick based on fused a-β corundum brick waste is provided, comprising the following steps:

[0029] 1) Put aggregate fused a-β corundum brick waste, 85 bauxite particles and admixtures into a mixing mill for premixing, then add andalusite fine powder, sillimanite fine powder, fused corundum fine powder, Guangxi white mud powder and water for mixing. When the mixed mud material has no mud lumps or white materials, it can be milled;

[0030] 2) The milled clay is formed into semi-finished bricks, which are then dried and sintered to obtain low creep high alumina bricks based on fused a-β corundum brick waste.

[0031] According to the above scheme, in step 1), the premixing time is 3 to 5 minutes; and the mixing time is 10 to 15 minutes.

[0032] According to the above scheme, in step 1), the amount of water added is 3-4% of the amount of all solid materials added.

[0033] According to the above scheme, in step 2), the milled clay is formed into semi-finished bricks by a friction press.

[0034] According to the above scheme, in step 2), the semi-finished bricks are required to have a dense appearance without cracks, honeycombs, or rough surfaces.

[0035] According to the above scheme, in step 2), the drying process is: treating at a temperature of 90 to 180° C. for 8 to 15 hours.

[0036] According to the above scheme, in step 2), the sintering process is: sintering at a temperature of 1460-1480° C. for 8-12 hours.

[0037] The present invention utilizes the properties of a-alumina and β-alumina components in the fused a-β corundum brick waste, and uses the fused a-β corundum brick waste with a particle size of 0 to 3.5 mm as the aggregate part of the material to form a strong corundum phase skeleton. a-Al2O3 can enhance the density and strength of the material structure skeleton, and the flat crystalline structure of β-Al2O3 forms a void structure on the material due to the loose lattice, which is more resilient than other Al2O3 phases. At the same time, it is further combined with a-Al2O3, mullite phase, etc. to form a staggered and robust structure, and a certain gap is formed between the skeleton structures, which can diffuse the energy of the absorbed thermal stress and form a buffer zone to avoid the excessive density of the structure, which makes the energy unable to be released in time, resulting in a sharp increase in the absorbed energy, thereby breaking the crystal bond, causing the material to break and peel off sharply, and then improving the thermal shock resistance of the material. The performance of the aggregate can be greatly improved by fused a-β corundum brick waste, and the amount of glass liquid phase brought in is reduced, so that the amount of liquid phase in the material is reduced under high temperature, the consistency is increased, and the occurrence of displacement of each phase is reduced. The entire material forms a structure of corundum phase-mullite phase-liquid phase-other impurity phases, in which the corundum phase and mullite phase occupy the dominant position, which strengthens the strength of the skeleton in the material structure and reduces the liquid phase slip of the matrix part of the material structure. At the same time, the large flat plate-like crystal morphology formed by β-Al2O3 not only strengthens its own strength, but also forms gaps, increasing the space for releasing external hard forces and improving thermal shock performance.

[0038] The beneficial effects of the present invention are as follows:

[0039] 1. The present invention provides a low creep high alumina brick based on fused a-β corundum brick waste, which uses fused a-β corundum brick waste and 85 bauxite particles as aggregates, and is combined with sillimanite fine powder, fused corundum fine powder and Guangxi white mud powder. The components have the same permeability synergistic effect and a reasonable organizational structure. The obtained low creep high alumina brick has a good microstructure, stable product quality, high compressive strength and good thermal shock resistance; wherein: the compressive strength is not less than 60MP, the creep rate is not higher than 0.6, the volume density is not less than 2.5, and the thermal shock resistance is not less than 30, which is far superior to similar high alumina bricks, greatly improves the performance of low creep high alumina bricks, and has important application prospects.

[0040] 2. The present invention utilizes the waste of fused a-β corundum bricks, which can replace part of bauxite while improving performance, reducing costs, solving the problem of such industrial waste treatment and recycling, and effectively alleviating the shortage of existing bauxite mineral resources, which has important environmental significance and economic value.

[0041] 3. The preparation process of the present invention is simple and the cost is low. The obtained high-alumina bricks have the characteristics of high strength, high volume density, low creep rate and good thermal shock resistance. They are effective in blast furnace hot blast furnaces and industrial kilns and have the potential for industrial application. DETAILED DESCRIPTION

[0042] The technical scheme in the embodiment of the present invention is described in detail below in conjunction with the embodiment of the present invention. The following implementation cases are only part of the embodiments of the present invention, rather than all the implementation cases. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0043] The relevant raw material indicators in the following examples of the present invention are as follows:

[0044] The waste fused a-β corundum bricks are mainly composed of a-Al2O3 and β-Al2O3 crystal phases, with a-Al2O3 accounting for 40-50wt%, β-Al2O3 accounting for 45-60wt%, wherein Al2O3≥93wt%, Na2O+K2O≤1wt%, Fe2O3≤1wt%, and particle size of 0-3.5mm; the waste fused a-β corundum bricks are recycled by the following method: the discarded fused a-β corundum bricks in the cutting and grinding process are picked up, separated and impurities are removed, then the fused a-β corundum bricks are steamed and washed 3-4 times, then blown and dried, and crushed into particles with a particle size of 0-3.5mm, and iron removal is carried out during the crushing and pulverizing process to control the Fe2O3 content within 1%.

[0045] 85 bauxite particles, Al2O3≥85wt%, Fe2O3≤1.5wt%, refractoriness≥1800℃, particle size of 0~3.5mm.

[0046] Andalusite fine powder, Al2O3≥55wt%, Fe2O3≤1.5wt%, particle size≤0.075mm;

[0047] Sillimanite fine powder, Al2O3≥56wt%, Fe2O3≤1wt%, particle size 0~0.2mm;

[0048] Fused corundum fine powder, Al2O3≥95wt%, Fe2O3≤0.2wt%, particle size≤0.075mm;

[0049] Guangxi white mud powder, Al2O3≥35wt%, Fe2O3≤1.5wt%, particle size≤0.075mm;

[0050] The admixture is dextrin.

[0051] Example 1

[0052] Provided is a low creep high alumina brick based on fused a-β corundum brick waste, wherein the raw material components are as follows by mass percentage:

[0053] 25wt% of fused a-β corundum brick waste, with a particle size of 0 to 3.5mm;

[0054] 85 bauxite particles 25wt%, particle size 0-3.5mm;

[0055] Andalusite fine powder 16wt%, particle size ≤ 0.075mm;

[0056] Sillimanite fine powder 14wt%, particle size 0-0.2mm;

[0057] Fused corundum fine powder 10wt%, particle size ≤ 0.075mm;

[0058] Guangxi white mud powder 10wt%, particle size ≤ 0.075mm;

[0059] 3.5% external admixture.

[0060] The method for preparing low creep high alumina bricks based on fused α-β corundum brick waste in this embodiment comprises the following steps:

[0061] All the above raw materials are mixed in a powerful mixer. Aggregate fused a-β corundum brick waste and 85 bauxite particles and admixtures are put into the mixer for pre-mixing for 4 minutes, and then andalusite fine powder, sillimanite fine powder, fused corundum fine powder, Guangxi white mud powder and water are added for mixing for 12 minutes. The amount of water added is 3.5% of the mass of all solid materials. The mixed mud material has no mud lumps and white materials, and can be milled. The mud material out of the mill is formed into semi-finished brick blanks by a friction press, which requires a dense appearance without cracks, honeycombs, pockmarks, etc. The semi-finished product is dried at 180℃ for 12 hours, and then sintered at 1480℃ for 10 hours to be a finished product.

[0062] Example 2

[0063] Provided is a low creep high alumina brick based on fused a-β corundum brick waste, wherein the raw material components are as follows by mass percentage:

[0064] 24wt% of fused a-β corundum brick waste, particle size 0-3.5mm;

[0065] 85 bauxite particles 26wt%, particle size 0-3.5mm;

[0066] Andalusite fine powder 12wt%, particle size ≤ 0.075mm;

[0067] Sillimanite fine powder 15wt%, particle size 0-0.2mm;

[0068] Fused corundum fine powder 11wt%, particle size ≤ 0.075mm;

[0069] Guangxi white mud powder 12wt%, particle size ≤0.075mm;

[0070] External admixture 3.3%.

[0071] The preparation process is as in Example 1.

[0072] Example 3

[0073] Provided is a low creep high alumina brick based on fused a-β corundum brick waste, wherein the raw material components are as follows by mass percentage:

[0074] 26wt% of fused a-β corundum brick waste, particle size 0-3.5mm;

[0075] 85 bauxite particles 26wt%, particle size 0-3.5mm;

[0076] Andalusite fine powder 16wt%, particle size ≤ 0.075mm;

[0077] Sillimanite fine powder 16wt%, particle size 0-0.2mm;

[0078] Fused corundum fine powder 11wt%, particle size ≤ 0.075mm;

[0079] Guangxi white mud powder 5wt%, particle size ≤0.075mm;

[0080] External admixture 4%.

[0081] The preparation process is as in Example 1.

[0082] Table 1 is a comparison table of performance indicators of low creep high alumina bricks of traditional brick brands and medium and high alumina bricks of Examples 1-3.

[0083] Table 1. Performance index comparison table of low creep high alumina bricks

[0084]

[0085] It can be seen from Table 1 that the low creep high alumina bricks prepared in the embodiment of the present invention have lower creep rate, higher compressive strength and better thermal shock resistance than traditional low creep high alumina bricks, which greatly improves the performance of low creep high alumina bricks, realizes the resource utilization of waste, reduces production costs, and is suitable for mass production.

[0086] It should be understood that those skilled in the art can make improvements or changes based on the above description, and all these improvements and changes should fall within the scope of protection of the appended claims of the present invention.

Claims

1. A low creep high alumina brick based on fused a-β corundum brick waste, characterized in that: The raw materials of the low creep high alumina brick include the following components by mass percentage: 20-30% of fused a-β corundum brick waste, with a particle size of 0-3.5mm; 85 bauxite particles 20-30%; Andalusite fine powder 10-20%; Sillimanite fine powder 10-20%; Fused corundum fine powder 0-15%; Guangxi white mud powder 0~15%; Admixture 2-5%, external mixing.

2. The low creep high alumina brick according to claim 1, characterized in that: The fused a-β corundum brick waste is mainly composed of a-Al2O3 and β-Al2O3 crystal phases.

3. The low creep high alumina brick according to claim 1, characterized in that: In the fused a-β corundum brick waste, Al2O3≥93wt%, Na2O+K2O≤1wt%, and Fe2O3≤1wt%.

4. The low creep high alumina brick according to claim 1, characterized in that: The waste fused a-β corundum bricks are recycled in the following way: the fused a-β corundum bricks discarded during the cutting and grinding process are picked up, separated and impurities are removed, then steamed and washed 3-4 times, then blown and dried, and crushed into particles with a particle size of 0-3.5 mm, and iron removal is performed during the crushing and pulverizing process.

5. The low creep high alumina brick according to claim 1, characterized in that: The particle size of the 85 bauxite particles is 0-3.5 mm; the particle size of the andalusite fine powder is ≤0.075 mm; the particle size of the sillimanite fine powder is 0-0.2 mm; the particle size of the fused corundum fine powder is ≤0.075 mm; and the particle size of the Guangxi white mud powder is ≤0.075 mm.

6. The low creep high alumina brick according to claim 1, characterized in that: In the 85 bauxite particles, Al2O3≥85wt%, Fe2O3≤1.5wt%, and refractoriness≥1800°C; in the andalusite fine powder: Al2O3≥55wt%, Fe2O3≤1.5wt%; in the sillimanite fine powder: Al2O3≥56wt%, Fe2O3≤1wt%; in the fused corundum fine powder: Al2O3≥95wt%, Fe2O3≤0.2wt%; in the Guangxi white mud powder, Al2O3≥35wt%, Fe2O3≤1.5wt%.

7. The low creep high alumina brick according to claim 1, characterized in that: The additive is dextrin or pulp.

8. A method for preparing low creep high alumina bricks based on fused α-β corundum brick waste according to any one of claims 1 to 7, characterized in that: The following steps are involved: 1) Put aggregate fused a-β corundum brick waste, 85 bauxite particles and admixtures into a mixing mill for premixing, then add andalusite fine powder, sillimanite fine powder, fused corundum fine powder, Guangxi white mud powder and water for mixing. When the mixed mud material has no mud lumps or white materials, it can be milled; 2) The milled clay is formed into semi-finished bricks, which are then dried and sintered to obtain low creep high alumina bricks based on fused a-β corundum brick waste.

9. The preparation method according to claim 1, characterized in that: In the step 1), the premixing time is 3 to 5 minutes; and the mixing time is 10 to 15 minutes.

10. The preparation method according to claim 1, characterized in that: In the step 2), the drying process is: treating at a temperature of 90 to 180° C. for 8 to 15 hours; and the sintering process is: sintering at a temperature of 1460 to 1480° C. for 8 to 12 hours.

Citation Information

Patent Citations

  • Refractory mortar and preparation method thereof

    CN109437939A

  • Low-creep high-alumina brick and preparation method thereof

    CN112457031A

  • Electrolytic cell

    FR2986012A1

  • Alumina molten cast refractory and manufacturing method therefor

    JP2015231929A